Eye movements in man and other animals. (September 2019) - Land, Michael
Abstract: Good vision requires a near stationary image if motion blur is to be avoided. All animals with good eyesight (principally the vertebrates, arthropods and cephalopod molluscs) have adopted a very similar strategy for achieving this: fixations in which gaze is kept still, with saccades to change gaze direction as fast as possible. In all these groups the stability of fixations is maintained by reflexes that oppose the effects of head or body movement (the vestibulo-ocular reflex in vertebrates), and that oppose drift of the image on the retina (optokinetic and optomotor reflexes). A small number of species of molluscs and arthropods have adopted a different strategy: allowing the retinas to scan across the surroundings to acquire information. The retinas in these animals are all linear structures a few receptors wide, and scan at right angles to their long dimension. The speed of scanning varies with retinal resolution, ensuring that scan speed does not produce deleterious blur.